(untitled) (Bangladesh Journal of Botany, 2025)
Bacterial polyhydroxyalkanoates (PHAs) are the most feasible substitute for fossil fuel based-plastics owing to their biocompatibility and biodegradability. The study was aimed to isolate and identify polyhydroxyalkanoates producing bacteria from various readily available and unusable waste materials. 75 bacterial isolates were identified as PHAs producers from the collected samples. Among them, 33 isolates were selected for their in-depth analysis and identification. All of the selected bacterial isolates were Gram positive rods except one. Considering morphological, biochemical, and physiological characteristics, isolated bacteria were provisionally identified. Interestingly, 32 isolates corresponded to the single genus Bacillus, whereas the remaining strain was Enterococcus sp. PHAs production was confirmed by the presence of key functional groups notably C=O, C-H, C-O, and –OH, respectively. Bangladesh J. Bot. 54(3): 483-489, 2025 (September)